Early and late analysis of postpartum stress in newborn foals - Cruz, R.K.S. [UNESP]; Alfonso, A. [UNESP]; Lourenço, M. L.G. [UNESP]; Souza, F. F. [UNESP]; Oba, E. [UNESP]; Ramos, P. R.R. [UNESP]; Chiacchio, S. B. [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate newborn foals stress in the first 48 hours of life. Heart rate (HR), heart rate variability (HRV) and serum cortisol concentrations, blood glucose, and lactate were determined in foals (n = 20, Paint Horse). Cortisol concentrations decreased significantly between four and 48 hours, with the highest concentration at 4 hours after birth. Positive correlations between cortisol and lactate occurred between 12 and 16 hours. And there was a negative correlation between cortisol and lactate 4 hours after birth. Among the values obtained for HR, there was significantly difference between the the value obtained at twelve hours of life moment and all the other moments measured, the highest values were at birth, 24 and 48 hours of life. Among HRV indexes, there were no statistical differences between the variables analysed. The cortisol, HR and HRV alterations were consistent to neonatal stress, but might be related to extrauterine environment adaptation associated to sympathoadrenal response, since those foals were healthy.
Keywords: Cortisol; Equine neonate; Heart rate; Heart rate variability